The Effect of Project-Based Learning on Students’ Achievement in Writing Narrative Text - Nurmahyuni Asrul; Sintia Friskila Rajagukguk; Veny Octaviana Sitepu; Pebi Maria Siregar; Abdurrahman Novri (Journal of English Language and Education, 2021)
The purpose of this research is to proof the effect of project-based learning model on students’ achievement in writing Narrative Text at grade X IPS SMA Pangeran Antasari Medan School students in 2021/2022.  This research was quasi-experimental with cause and effect relationship by involving the control-class and the experimental-class. The two classes were given pretest and post-test. The result showed mean of the experimental class was from 56.05 to 80.2 and the controlled class was from 62.1 to 74.0. From hypothetical tests, the significance T-test Sig (p)0.035(a)0.05 and that means Ha 0,05.The controlled class score increased from 62.1 to 74.05 and the critical contrast between the mean scores in controlled class (M 74.055, SD 9.8688), while the experimental class (M 80.159, Sd 8.7281), t(42) 2.173 , p 0.035 d 0.655 ) and tcount 2.137 t????????????le 2.019. By using a project-based-learning model in writing narrative text, the students can investigate and hone their capacity and creativity in writing It demonstrated that the Project-based learning models has given a solid impact on students’ achievement in writing narrative text. The Project-based-learning (PJBL) model effected the students’ achievement in writing.